VersaStack solution by Cisco and IBM with IBM DB2, IBM Spectrum Control, and IBM Spectrum Protect - Tate, Jon (IBM redbooks., 2016)
Aimed at experienced storage administrators, this IBM Redbooks publication will help those that are tasked with deploying a VersaStack solution with IBM DB2 High Availability (DB2 HA), IBM Spectrum Protect, and IBM Spectrum Control. --